Quantificação de compostos fenólicos nas folhas de Humulus lupulus L. (lúpulo) - Albara, Sheila Prescendo (2022)
Hops is a plant of the genus Humulus that belongs to the Cannabaceae family. There are three species of plants in the genus Humulus, which are Humulus lupulus L., H. japonicus, and H. yunnanensis Hu. Hops have always been cultivated in Germany and the United States, as these places would have suitable conditions for cultivation. In Brazil, it has recently started to be cultivated with the aim of establishing self-sufficiency in production, as it is widely used in the brewing industry. In addition, some biological effects of the plant have been reported, with emphasis on the anti-inflammatory, antioxidant, antimicrobial effect and also the influence on the metabolic syndrome. Since hop flowers are used in the brewing industry and the leaves are discarded, this work evaluated precisely these leaves. It is known that hops contain phenolic compounds, which are substances from the secondary metabolism of plants with recognized biological activity. In this sense, this work aimed to quantify phenolic compounds in ethanolic extract of leaves of Humulus lupulus variety Columbus, by the Folin-Ciocalteu method. The results were expressed in milligrams of gallic acid equivalent (EAG) per gram of dry extract, with hop leaf extract having 29.25 mg EAG g -1 . In the literature, studies with the cones of the plant show a higher phenolic content than in the leaves. However, the results showed that the leaves can also be a source of compounds of pharmacological interest. The variations that may occur in the final results due to environmental factors and differences in the preparation of extracts are highlighted.